Digital image watermarking using partial pivoting lower and upper triangular decomposition into the wavelet domain. Issue 9 (1st September 2015) - Muhammad, Nazeer; Bibi, Nargis
Abstract : A digital image watermarking algorithm using partial pivoting lower and upper triangular (PPLU) decomposition is proposed. In this method, a digital watermark image is factorised into lower triangular, upper triangular and permutation matrices by PPLU decomposition. The permutation matrix is used as the valid key matrix for authentication of the rightful ownership of the watermark image. The product of the lower and upper triangular matrices is embedded into particular sub‐bands of a cover image that is decomposed by wavelet transform using the singular value decomposition. The weightage‐based differential evolution algorithm is used to achieve the possible scaling factor for obtaining the maximum possible robustness against various image processing operations and pirate attacks. The authors experiments show that the proposed algorithm is highly reliable with better imperceptibility of the embedded image and computationally efficient compared with recently existed methods.